Gaspery-Jacques Roberts’ Anxiety in Emily St. John Mandel’s Sea of Tranquility - Salsabilla Damayanti Samal; Danu Wahyono (Proceeding of Conference on Literature, Linguistic, and Cultural Studies, 2026)
This study is entitled “Gaspery-Jacques Roberts’ Anxiety in Emily St. John Mandel’s Sea of Tranquility”. The objective of this research is to examine the anxiety experienced by Gaspery-Jacques Roberts, the main character of the novel. It uses a qualitative descriptive method and a psychological approach to literature, applying Sigmund Freud’s psychoanalytic theory as the framework. This study aims to identify the causes of Gaspery’s anxiety, examine its effects on his character development, and portray how he copes with it throughout the story. The results show that Gaspery’s anxiety is caused by helplessness over the loss of his mother and his failed marriage, the danger-situation of investigating a reality-threatening anomaly, the loss of important people such as Talia, and the ego’s fear of the super-ego produced by breaking the protocol of the Time Institute. These causes affect his feeling, thinking, and acting, moving him from emotional numbness toward calmness and longing for connection, from panic toward moral clarity and philosophical acceptance, and from passive withdrawal toward decisive action. There are several ways Gaspery copes with his anxiety, namely avoidance, reasoning, action, and acceptance. From the results of this study, the findings indicate that Gaspery successfully transforms the anxiety that has shaped his life into a force that leads him toward moral growth, culminating in his quiet acceptance of both his choices and the uncertain nature of his reality.